2020
DOI: 10.3390/ijms21218194
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Connexin Gap Junctions and Hemichannels by Calcium and Calcium Binding Protein Calmodulin

Abstract: Connexins are the structural components of gap junctions and hemichannels that mediate the communication and exchange of small molecules between cells, and between the intracellular and extracellular environment, respectively. Connexin (Cx) 46 is predominately expressed in lens fiber cells, where they function in maintaining the homeostasis and transparency of the lens. Cx46 mutations are associated with impairment of channel function, which results in the development of congenital cataracts. Cx46 gap junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 87 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Recent studies have reported that Alizarin red-stained calcium precipitates are correlated with the morphology of nuclear opacity in mouse Cx46fs380 homozygous mutant lenses 38 ; the Cx50D47A mutant lenses show a similar distribution in the lens core with enriched calcium precipitates in the anterior Y-suture regions 39 . Connexin mutations disrupt calcium homeostasis and cause biomineralization in cataract formation 40 , 41 . This work indicates that age-related progression of Cx46KO nuclear cataracts is correlated with the age-related increase of calcium precipitates in Cx46KO lens cores, especially in the anterior Y-suture regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that Alizarin red-stained calcium precipitates are correlated with the morphology of nuclear opacity in mouse Cx46fs380 homozygous mutant lenses 38 ; the Cx50D47A mutant lenses show a similar distribution in the lens core with enriched calcium precipitates in the anterior Y-suture regions 39 . Connexin mutations disrupt calcium homeostasis and cause biomineralization in cataract formation 40 , 41 . This work indicates that age-related progression of Cx46KO nuclear cataracts is correlated with the age-related increase of calcium precipitates in Cx46KO lens cores, especially in the anterior Y-suture regions.…”
Section: Discussionmentioning
confidence: 99%
“…Opening of HCs is modified by connexin phosphorylation or by intracellular Ca 2+ concentrations [ 110 , 115 , 116 ]. In fact, moderate increments in intracellular Ca 2+ can promote HC opening by direct or indirect mechanisms, such as direct Ca 2+ /Calmodulin binding to Cx43 or by the activation of protein kinases [ 118 ]. More often, HCs are activated under pathological conditions, including oxidative stress, mechanical stretch, inflammatory processes, and lower pH.…”
Section: Structure Function and Regulation Of Gjc And Hcsmentioning
confidence: 99%
“…It has been reported that Cx46 in the lens interacts with Ca 2+ -calmodulin (CaM) and that a Cx46 mutant (G143R) associated with cataracts in humans enhances the Cx46-CaM interaction and forms gap junction channels and hemichannels with altered voltage gating and permeability ( Hu et al, 2018 ). From these results, it has been suggested that the alteration in Cx46-CaM interaction can mediate the deleterious effect of some Cx46 mutations in lens fiber cells ( Figure 3 ) ( Hu et al, 2020 ).…”
Section: Cx46 Posttranslational Modifications and Their Potential Rel...mentioning
confidence: 96%